ANTIOXIDANT AND ANTICANCER PROPERTIES OF ACACIA NILOTICA LEAF EXTRACT (International Journal of Food and Nutritional Sciences, 2022)
Medicinal plants are rich sources of herbal properties contributing in the discovery of new drugs towards various disorders, diseases including cancer without any toxic effects on the individuals treated. Acacia nilotica is widely used as tradition medicine such as for the treatment of venereal diseases, burns, wounds, stomachache etc. This study focuses on the antioxidant and anticancer properties of Acacia nilotica leaves methanolic extract. Two antioxidant assays i.e., DPPH assay and ABTS assay were assigned to study the antioxidant potential of the leaf extract of Acacia nilotica. The anticancer activity was also studies on the MCF 7 and 3T3 cancer cells through the MTT assay and dual acridine orange/ethidium bromide fluorescent staining. The studied leaf sample had a potential anti-oxidant and anti-cancer potential as it gave significant positive results for both the activities. Leaves part of Acacia nilotica had higher antioxidant activity at 90 µg/ml concentration in DPPH assay. In ABTS scavenging activity of leaves, highest activity showed at 100 µg/ml concentration. Accordingly, Acacia nilotica leaves extract was more effective to inhibit MCF 7 breast cancer cell line compared to 3T3 cell lines as the percent cell viability of MCF 7 breast cancer cell line at 10µg/ml leaves extract was recognized 92.48 % while it was 96.08 % cell viability at 25µg/ml for 3T3 cells. Acacia nilotica can be a better candidate for isolation of cytotoxic and anticancer compounds especially for methanol extract. Therefore, from the results obtained Acacia nilotica plays an important role in the prevention and management of various diseases. It can be used in future as herbal drugs with ecofriendly, non-expensive and without any side effects.